Robust output regulation and model following of uncertain networked systems. Issue 6 (3rd June 2021) - Rahmani, Behrooz
Abstract : This paper proposes a robust output feedback-based controller for a class of uncertain linear network-based control systems. This method ensures the stability, robustness and an output regulation against the modelling uncertainties and communication network negative effects. In this way, a switching sliding surface is proposed and designed using a switched quadratic Lyapunov functional, by solving a set of linear matrix inequalities. A method is then proposed to reach the quasi-sliding mode and stay thereafter. Simulation studies on four benchmark problems show the effectiveness of the proposed method with respect to the model uncertainties and also band-limited communication network deficiencies.